Analisis Perilaku Siswa yang Menyimpang di Tinjau dari Lokasi Geografis Budaya Aceh Bersyari’at - Chairul Bariah; Erna Fitriani Hamda (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2021)
Acehnese people are known for their syari’ah customsDeviant behavior of children is a social problem that often arises in Indonesia, especially in Aceh, which is a problem that is quite worrying and causes a lot of children's behavior to deviate from Islamic law. In this study, it was taken from 2 samples at SMU Negeri 4 Banda Aceh and the Institute for Special Development for Children (LPKA). This study used a descriptive qualitative approach and data collection using observation and direct interviews. Based on the results of observations and interviews, the cause of children committing deviant actions was due to several factors, especially the lack of parental attention which occurred especially in the case of children in LPKA. The role of parents that must be applied in overcoming deviant children's behavior is to provide religious education to children, familiarize children with Islamic cultures and provide role models for children. Parents should be good role models and noble characters, and must also explain and give students the importance of maintaining and maintaining and living in a style that is in accordance with Islamic teachings. So that children will instill in themselves a Shari’ah culture that can avoid themselves from deviating from the Sharia culture.